The Effects of G-CSF on Proliferation of Mouse Myocardial Microvascular Endothelial Cells - Li, Jiming (Molecular Diversity Preservation International (MDPI), 2011)
This paper explores the effect of granulocyte colony-stimulating factor (G-CSF) on mouse myocardial microvascular endothelial cell (CMECs) proliferation. CMECs were harvested from C57/BL6 mice. CMECs were cultured in medium containing G-CSF (0 ng/mL, 20 ng/mL, 40 ng/mL, 60 ng/mL) for five days. Proliferative activity of CMECs was examined by CCK-8 method. Hypoxia inducible factor-1 (HIF-1) and p53 expression levels was determined from the mRNA obtained by reverse transcription polymerase chain reaction (RT-PCR). Results showed that the purity quotient of the CMECs, which were cultured by the method of modified myocardial tissue explant culture, was higher than 95%. Compared with control untreated cells, the proliferative activity of CMECs and the expression level of HIF-1 mRNA in these cells were enhanced by G-CSF treatment, whereas the expression level of p53 mRNA was markedly reduced. It may be concluded that G-CSF could promote the proliferative activity of CMECs, which might be mediated by upregulation of HIF-1 and downregulation of p53.